Associations of four obesity indices with diabetes mellitus in Korean middle-aged and older adults using the Korean Genome and Epidemiology Study (KoGES) - Yiseul Lee; Nam-Kyoo Lim; Hyun-Young Park (BMC Public Health)
Abstract Background Obesity is associated with a high risk of diabetes mellitus (DM); therefore, obesity-related indices are strongly associated with DM. This study evaluated the association of obesity indices, including body mass index (BMI), waist circumference (WC), waist-to-hip ratio (WHR), and a body shape index (ABSI), with DM in Korean middle-aged and older adults. Methods Data from three population-based cohorts (Ansan and Ansung, Health Examinee, and Cardiovascular Disease Association Study, derived from the Korean Genome and Epidemiology Study) were analyzed. Logistic analysis was used to evaluate the association of BMI, WC, WHR, and ABSI with DM, after adjusting for covariates according to sex and age. The integrated discrimination index (IDI) and category-free net reclassification improvement (cfNRI) and area under the curve (AUC) of the receiver operating characteristic (ROC) curve were analyzed by age group to investigate index-specific model performance. Results Among the 160,585 participants, 13,846 had DM (6,837; men [11.86%] and 7,009 women [6.81%]). Age increase was associated with an increased prevalence of DM: 2,339 (4.01%), 5,313 (8.74%), and 6,194 (14.93%) in the 40–49, 50–59, and ≥ 60 years age groups. After adjusting for covariates, the odds ratios (OR) for DM of WHR and WC were higher than those of the other indices in every age group. However, the OR for WHR, WC, and BMI decreased with age in both sexes. ABSI showed steady and slightly increasing ORs with increasing age although the ORs in both sexes were generally low for DM. For IDI and cfNRI, WHR had the highest values among all age groups. The AUC of the ROC curve showed that the WHR had the highest value in all age groups. Conclusion The WHR had the strongest association with DM, but was not a good DM index in older people. Therefore, age-related index criteria for DM, especially in women, were needed for the effective prevention and management of DM.